Health Medical Tourism: The Present and the Future - OSADCHUK, Mikhail A.; OSADCHUK, Alexey M.; SOLODENKOVA, Karina S.; TRUSHIN, Maxim V. (Journal of Environmental Management and Tourism, 2020)
Development of intergovernmental policy on health tourism is cross-industrial, with medical services acting as a promoting factor. Health tourism ideology is based on interconnection between the natural environment, transport availability, healthcare system and people. During health tourism travels people get in close contact with the environment in order to feel physical and psychological comfort without direct medical treatment. Health tourism is supposed to become the basis for alternative therapy and remain progressive. Meanwhile, dominating cultural aspects must provide competitive advantages related to non-clinical factors. Satisfactory health tourism can be achieved only with the help of a team of specialists having certain experience in both clinical and non-clinical healthcare.